MODELING AND SIMULATION OF AN AIRCRAFT ELECTRICAL POWER SYSTEM (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Although recent developments in aircraft electrical technology have had a significant impact on aircraft electrical power systems (EPS), thus reminding the development and production of more electric aircraft (MEA), but also important steps in the development of all-electric aircraft (AEA), still the EPS of the latest aircraft produced by the two big players in the market, the Neo series from Airbus and the NG or Max from Boeing respectively, is completely traditional – a constant speed constant frequency (CSCF) system. Thus, for an alternating current one, it is composed of the power source – the integrated drive generator (IDG), the command and control system – the generator control unit (GCU), the transmission and distribution system, the protection system – the CBs (circuit breaker) and electrical loads. This paper presents the design and simulation of an aircraft EPS using Simulink’s Simscape package, a MATLAB program, and for the first time in the specialized literature, a model of the constant speed drive (CSD) generated with the same program is used to drive the synchronous generator (SG) in the IDG.
Keywords: All-electric aircraft (AEA); Automatic frequency regulator (AFR); Automatic voltage regulator (AVR); Brushless synchronous generator (BSG); Constant speed constant frequency (CSCF); Constant speed drive (CSD); Electrical power systems (EPS); Generator control unit (GCU); Integrated drive generator (IDG); More electric aircraft (MEA); Proportional integral derivative (PID); Synchronous generator (SG); Variable speed constant frequency (VSCF); Variable speed variable frequency (VSVF)